2022
DOI: 10.3390/ijerph19053095
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Features Impacting Respiratory Diseases in Urban Areas

Abstract: Air pollution exposure has become ubiquitous and is increasingly detrimental to human health. Small Particulate matter (PM) is one of the most harmful forms of air pollution. It can easily infiltrate the lungs and trigger several respiratory diseases, especially in vulnerable populations such as children and elderly people. In this work, we start by leveraging a retrospective study of 416 children suffering from respiratory diseases. The study revealed that asthma prevalence was the most common among several r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In our prior work [31], a novel approach was developed to create the MoreAir data set, aiming to examine the impact of multiple factors on air pollution levels. This unique data set was initially developed to investigate the potential relationship between environmental conditions and the respiratory health of asthma patients in their living environments.…”
Section: B the Moreair Project And Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior work [31], a novel approach was developed to create the MoreAir data set, aiming to examine the impact of multiple factors on air pollution levels. This unique data set was initially developed to investigate the potential relationship between environmental conditions and the respiratory health of asthma patients in their living environments.…”
Section: B the Moreair Project And Data Setmentioning
confidence: 99%
“…To address concerns about the accuracy and reliability of the sensors used for air quality monitoring, an extensive evaluation was conducted in an earlier study [31]. Lowcost sensors, while cost-effective, often face challenges related to calibration, operational stability under various meteorological conditions, and intramodel variability.…”
Section: B the Moreair Project And Data Setmentioning
confidence: 99%
“…[6–8] Numerous forms of atmospheric pollutants, such as NO 2 , carbon monoxide, CO 2 , SO 2 , and ozone (O 3 ), have been shown to have a substantial correlation with asthma occurrences and exacerbations. [9–17]…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Numerous forms of atmospheric pollutants, such as NO 2 , carbon monoxide, CO 2 , SO 2 , and ozone (O 3 ), have been shown to have a substantial correlation with asthma occurrences and exacerbations. [9][10][11][12][13][14][15][16][17] It has been extensively observed that elevated ozone levels have an inflammatory impact on the respiratory system, which likely contributes to the progression of asthma. [12,18,19] The connection between low to moderate ozone levels and asthma, on the other hand, has received less attention.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution is described as the presence of substances in the air that are harmful to humans and linked to a higher risk of diseases [1][2][3][4][5], such as asthma, as a result of increased airway hyperresponsiveness. Various types of air pollutants, such as particulate matter (PM), nitrogen dioxide (NO 2 ), carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), and ozone (O 3 ), have been found to trigger or exacerbate asthma attacks [6][7][8][9][10][11][12][13]. It is widely accepted that these air pollutants are emitted from various sources, including vehicles, manufacturing industries, and waste deposits.…”
Section: Introductionmentioning
confidence: 99%